Usability Evaluation of Pandemic Health Care Mobile Applications. Issue 1 (March 2021) - Mubeen, M; Iqbal, M W; Junaid, M; Sajjad, M H; Naqvi, M R; Khan, B A; Saeed, M M; Tahir, M U
Abstract: This study was conducted to evaluate the usability of health care apps and its significance in the field of health care. As health care centers are the settings working 24/7 for providing health services to patients. For this study a systematic review, comparison and functionality assessment of selected COVID19 mobile apps was performed. The assessment was performed on two digital platforms, App store on Apple iPhone and Google play store on Android smartphones. Further online search of keywords on Google was also conducted in order to ensure the reliability and validity of apps on these stores. And only those apps were selected which were in English because of the language proficiency of authors. The mobile apps selected were having five features of assessment, a questionnaire, Privacy statement, Precautionary measures if test positive for COVID19, after plans of Pandemic and Region based. The sample was a blend of participants from different fields including students, doctors, patients and software developers. This is quantitative study; a questionnaire was distributed among the selected participants who were familiar with the use of health care mobile apps. The data was analyzed on the basis of gender and age. The results were made on the basis of responses towards effectiveness, efficiency and satisfaction of users towards mobile phone apps. The results show that apps were found 64.5% informative for participants as they helped in fast communication of doctors and patients while sitting at the other corner of world.